Xylophagous insects (Insecta: Coleoptera, Hymenoptera, Lepidoptera) of Populus sp. (Malpighiales: Salicaceae) in the eastern regions of Ukraine - Skryknyk, Yu. Ye.; Zhupinska, K. Yu.; Koshelyaeva, Ya. V.; Meshkova, V. L. (The Kharkiv Entomological Society Gazette, 2023)
72 species of xylophagous insects were identified under the bark and in the wood of poplars and aspens, including Coleoptera (66 species), Lepidoptera (5 species), and Hymenoptera (1 species). There were 40 Cerambycidae, 19 Buprestidae, 7 Curculionidae, 2 Sesiidae, 3 Cossidae, 1 Siricidae species. 5 monophagous, 14 oligophagous, and 53 polyphagous insects were identified. The frequency of occurrence of all species is estimated. Single and rare species predominate (33 and 26 species, respectively). There were 9 common species and 4 abundant species. All abundant species are polyphagous. 3 figs, 1 tab., 46 refs.
Keywords: poplars and aspen; stem pests; frequency of occurrence; trophic specialization